Energy management for Tamil Nadu, India - Chan, Yi Teng. (2012)
With the growing demand for energy, and subsequently growing greenhouse gas emissions, it is vital to explore alternative cleaner sources of energy and incorporate them into the existing power system before the global resources are depleted and damaged beyond recovery. This report targets one of the two emerging giants, India, and will explore the integration of renewable resource generation into the power grid, utilizing the smart grid technology. The integration will be investigated through simulation using the HOMER software to obtain the optimum system based on cost of electricity and emissions. The simulated scenario is based in Tamil Nadu, a southern state of India, and the targeted population will be approximately 0.001% of the state’s population, at about 7220 people. Renewable generation that will be explored includes solar and wind energy to complement the existing thermal generation plants. The integration will be further supported by demand and supply side management policies, and the effectiveness of these policies will be analyzed and enhanced using game theory.